2014
DOI: 10.2139/ssrn.2463865
|View full text |Cite
|
Sign up to set email alerts
|

The Hubris Hypothesis: Empirical Evidence

Abstract: The Hubris Hypothesis is grounded on a failure to adequately account for the winner's curse, which leads to overbidding. Surprisingly few papers have attempted to develop a direct empirical test of the presence of overbidding in M&A contests. We develop two such tests in this paper. Our results strongly support the existence of overbidding.JEL classification: G34

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…De Bodt et al (2014) examined 977 companies that made purchases in the USA and stated that 95% of them were successful. It has been revealed that acquiring firms bid more than the amount that maximises the shareholder value of the target firm.…”
Section: The Effect Of Managers' Overconfidence On Merger and Acquisi...mentioning
confidence: 99%
“…De Bodt et al (2014) examined 977 companies that made purchases in the USA and stated that 95% of them were successful. It has been revealed that acquiring firms bid more than the amount that maximises the shareholder value of the target firm.…”
Section: The Effect Of Managers' Overconfidence On Merger and Acquisi...mentioning
confidence: 99%